Pola Pencarian Data Investigasi di Media Online - Tika Rizkina Azizah; Septiawan Santana; Firmansyah (UNISBA Press, 2021)
Abstract. In investigative journalism work, there are three general forms of investigative methods, namely, related to the work of investigating documents, as well as investigations of individual subjects related to the problem. This general form of investigative reportage is termed a paper trail, people trail, and money trail. Tempo Magazine is a media that is considered to have competence and credibility for investigative coverage. Tempo magazine is a pioneer of investigative journalism in the period after 1990. In addition, the internet media has opened up information expansion based on a multidimensional